Adhesion of erythrocytes to endothelial cells after acute exercise: differences in red blood cells from juvenile and adult rats - Temiz Artmann, A; Akhisaroglu, M; Sercan, Z; Resmi, H; Kayatekin, B M; Yorukoglu, K; Kirkali, G (Physiological research, 2006)
Erythrocytes (RBC) from untrained male Wistar rats and rat glomerular endothelial cells (EC) were used to investigate the effects of acute exercise (speed: 20 m/min, slope: 0, duration: 1 hour) on RBC membrane protein oxidation and adhesion to cultured EC. Experimental animals were divided into juvenile (age 10 weeks) and adult (age 30 weeks) groups for these studies. Immediately following exercise, juvenile rat RBC membrane protein oxidation was significantly enhanced. Adult rat RBC showed significantly higher basal protein oxidation than juvenile RBC; but the level of adult rat RBC membrane protein oxidation was unaffected by exercise. Prior to exercise, adult rat RBC showed significantly higher adhesion to EC than RBC of juvenile rat. There was no difference in plasma fibronectin or fibrinogen levels following exercise. Only juvenile rat RBC showed a significant decrease in sialic acid residue content following exercise. These experiments show that there are changes in RBC-EC interactions following exercise that are influenced by animal age.
Keywords: tělesná námaha; Erythrocytes; oxidace-redukce; věkové faktory; Erythrocyte Membrane; krysa rodu Rattus; N-Acetylneuraminic Acid; Cell Adhesion; zvířata; Cells, Cultured; potkani Wistar; fibrinogen; Fibronectins; Endothelial Cells; Rats, Wistar; Male; erytrocytární membrána; kultivované buňky; erytrocyty; endoteliální buňky; Oxidation-Reduction; Rats; fibronektiny; buněčná adheze; kyselina N-acetylneuraminová; Age Factors; Animals; mužské pohlaví; Fibrinogen; Physical Exertion